P374Expression pattern of sarco (endo) plasmic reticulum calcium atpases (SERCA) isoforms in normal and diseased mouse cardiovascular tissues. (15th July 2014) - Blirando, K; Lipskaia, L; Keuylian, Z; Rouxel, C; Blaise, R; Adnot, S; Hajjar, RJ; Chemaly, ER; Limon, I; Bobe, R
Abstract: The sarco(endo) plasmic reticulum Ca2+ ATPases (SERCA) system is a key regulator of calcium cycling and signaling in cardiac and vascular myocytes and is composed of several isoforms. We aimed to characterize 1) the expression of the different SERCA isoforms in normal mouse cardiovascular tissues and 2) the modulation of the SERCA isoform system during cardiovascular pathologies (heart failure and/or atherosclerosis). Five SERCA isoforms - 2a, 2b, 3a, 3b and 3c were detected by RT-PCR and immunoblot in normal mouse heart and thoracic aorta. Absolute mRNA quantification (Table) confirmed that SERCA2a was the predominant isoform in the heart (∼99% of total SERCA mRNA) whereas the ubiquitous isoform SERCA2b represents less than ∼0.1%. Within cardiomyocytes (CM), SERCA2a and 2b were co-localized in the longitudinal SR, whereas SERCA3b was located at the junctional reticulum. In the aorta, SERCA2a accounted for ∼86.0% and SERCA2b for ∼7%. Among SERCA3 isoforms (3a, 3b and 3c), SERCA3b was the most expressed (∼6.5%) and was predominantly found in endothelial and vascular smooth muscle cells (VSMC), together with SERCA2a and 2b. In failing CM the SERCA2a expression was 2-fold down-regulated (from 9.65 to 5.01 pg/10 ng of total mRNA). Furthermore, both SERCA2a and SERCA2b were re-localized from longitudinal to junctional SR. A strong down-regulation of SERCA2a was also observed in atherosclerotic vessels (from 0.27 to 0.13 pg/10 ng of total mRNA) containing mainly synthetic VSMC; the proportion of both SERCA2b and SERCA3b increased to reach 8% and 7% respectively. In summary, we established that 1) the overall expression of SERCA mRNA is ∼ 50 fold higher in the heart compared to vascular tissues; 2) although several SERCA isoforms are expressed in cardiovascular tissues, SERCA2a is the major isoform in both cardiac and vascular myocytes; 3) nearly half the amount of SERCA2a mRNA is measured in both failing cardiomyocytes and synthetic VSMCs compared to healthy tissues. Together with the evidence of SERCA2a delocalization from longitudinal reticulum in hypertrophied cardiomyocytes, our study prove that SERCA2a is the principal regulator of excitation-contraction coupling in both CMs and contractile VSMCs and also supports a dynamic and integrated regulation of the SERCA isoform system, which deserves further studies.